Perilaku Bullying dan Pengaruhnya terhadap Prestasi Belajar Peserta Didik Sekolah Dasar: Bullying Behavior and its Effect on Elementary School Students' Learning Outcomes - Novitasari, Novitasari; Rahmadina, Safina Aslam (Dirasat Islamiah: Jurnal Kajian Keislaman, 2023)
A safe and comfortable environment is certainly needed for students to achieve maximum learning outcomes during the education process. However, in reality, in schools, we can still find acts of violence between friends or what is often called bullying. The purpose of this study was to determine the form of bullying that occurs in schools, a description of student learning achievement, and the effect of bullying on student learning achievement. This study uses a quantitative approach with a descriptive research type. The population was 150 students of Badean 01 Elementary School, with a sample of 30 students. The data collection technique used a questionnaire. Data analysis used descriptive statistics, data validity tests used classical assumption tests, and hypothesis tests used simple linear regression. The results of this study indicate that bullying behavior has no effect on student learning achievement. This is because the bullying that occurs in this school is included in the mild category. In addition, motivation, self-confidence, social support, and student intelligence, as well as teacher efforts are included in the fairly good category in handling bullying.